Risk of relapse phenotype recurrence in multiple sclerosis. (October 2014) - Kalincik, Tomas; Buzzard, Katherine; Jokubaitis, Vilija; Trojano, Maria; Duquette, Pierre; Izquierdo, Guillermo; Girard, Marc; Lugaresi, Alessandra; Grammond, Pierre; Grand'Maison, Francois; Oreja-Guevara, Celia; Boz, Cavit; et al.
Objectives: The aim was to analyse risk of relapse phenotype recurrence in multiple sclerosis and to characterise the effect of demographic and clinical features on this phenotype. Methods: Information about relapses was collected using MSBase, an international observational registry. Associations between relapse phenotypes and history of similar relapses or patient characteristics were tested with multivariable logistic regression models. Tendency of relapse phenotypes to recur sequentially was assessed with principal component analysis. Results: Among 14, 969 eligible patients (89, 949 patient-years), 49, 279 phenotypically characterised relapses were recorded. Visual and brainstem relapses occurred more frequently in early disease and in younger patients. Sensory relapses were more frequent in early or non-progressive disease. Pyramidal, sphincter and cerebellar relapses were more common in older patients and in progressive disease. Women presented more often with sensory or visual symptoms. Men were more prone to pyramidal, brainstem and cerebellar relapses. Importantly, relapse phenotype was predicted by the phenotypes of previous relapses. (OR = 1.8–5, p = 10 -14 ). Sensory, visual and brainstem relapses showed better recovery than other relapse phenotypes. Relapse severity increased and the ability to recover decreased with age or more advanced disease. Conclusion: Relapse phenotype was associated with demographic and clinical characteristics, with phenotypic recurrence significantly more common than expected by chance.